Strategies to Improve Antineoplastic Activity of Drugs in Cancer Progression - Stefanachi, Angela (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
The aim of this Special Issue is to collect reports regarding all the recent strategies, directed at the improvement of antineoplastic activity of drugs in cancer progression, engaging all the expertise needed for the development of new anticancer drugs: medicinal chemistry, pharmacology, molecular biology, and computational and drug delivery studies.